Market and system operator simulator integrating complex bids and network constraints using simulated annealing - Bruno André Pereira Santos Gomes (2006)
This paper describes a Market and System Operator Simulator to deal with complex bids and with network technical constraints. Complex bids allow market players to communicate requirements expressing inter-temporal constraints related for instance with ramps or with the minimum revenue to be obtained along a day. This kind of constraints leads to a larger optimization problem in the sense that hourly power matching problems get coupled. On the other side, the hourly dispatches identified by the Market Operator can imply violations of the power system security constraints, related for instance with voltage or power flow limits. Changing a particular hourly dispatch can originate violations of the inter-temporal constraints, thus suggesting that the problem should be handled in a more integrated way. Once the hourly dispatches are identified, and if any violation occurs, a probabilistic based algorithm - Simulated Annealing - is run to search for a feasible solution that is simultaneously adequate from the point of view of the Evaluation Function of the problem. The paper includes a case study using the IEEE 24 bus/38 branch system to illustrate the implemented algorithm and the potential of the model.